Understanding the preferential oxidation of carbon monoxide (PrOx) using size‐controlled Au nanocrystal catalyst. Issue 8 (5th July 2018) - Beck, Arik; Yang, An‐Chih; Leland, Amelia R.; Riscoe, Andrew R.; Lopez, Francisco A.; Goodman, Emmett D.; Cargnello, Matteo
Abstract : Removing CO from hydrogen streams is an important industrial process. The catalytic preferential oxidation of CO (PrOx) is a promising method for CO removal, leaving the hydrogen concentration unchanged. Here, the effect of size and support on the gold‐catalyzed PrOx reaction using size‐controlled Au nanocrystals (NCs) is investigated. For all supports, Au NC sizes of 2–5 nm show the highest rates, whereas for larger sizes rates drop. Ceria‐supported Au shows by far the best performance. By analyzing the dependency of the reaction rate on the NC diameter, the most active centers for CO oxidation on Au/CeO2 are Au + corner atoms at the interface with the support, resulting in 2.1 nm Au NCs supported on ceria reaching full O2 conversion and CO selectivity of about 50%. Therefore, it is suggested that increasing the fraction of Au‐ceria interface sites would lead to the best performing materials for this reaction. © 2018 American Institute of Chemical Engineers AIChE J, 64: 3159–3167, 2018